New coumarins from Pterocaulon polystachyum - Vera, Nancy Roxana (2001)
Aerial parts of Pterocaulon polystachyum from Chaco province, Argentina, afforded the known coumarins ayapin, isoscopoletin, prenyletin, prenyletin methyl ether, virgatenol, obtusinin, 5-methoxy-6,7-methylenedioxycoumarin, 5-(3,3-dimethylallyloxy)-6,7-methylenedioxycoumarin, 5-(2′,3′-dihydroxy-3-methylbutanoxy)-6,7-methylenedioxycoumarin, haplopinol methyl ether, 6-(1,1-dimethyl-2-propenyl)-7-hydroxycoumarin and demethylnieshoutin; the last two are new as natural products while the five new coumarins from the collection were isovirgatenol, 3′-deoxyobtusinin, 6-methoxy-7-(2′-hydroxyethoxy)-coumarin, 5-(2′-hydroxyethoxy)-6,7-methylenedioxycoumarin and a substance tentatively identified as 5-hydroxy-6,7-methylenedioxy-8-(3,3-dimethylallyl)-coumarin.